Carbon nanotube conductive binder and synthesis and application thereof
By using the carbon nanotube conductive adhesive CNT-PANM in the silicon-based anode of lithium-ion batteries, the problems of volume expansion, SEI film instability and insufficient conductivity of the silicon-based anode are solved, and higher cycling performance and energy density are achieved.
Patent Information
- Application Number
- CN202411913945.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-24
- Publication Date
- 2025-04-04
AI Technical Summary
The silicon-based negative electrode has stress problems caused by volume expansion in lithium-ion batteries, instability and insufficient conductivity of the SEI film, which affects the cycling performance and energy density of the battery.
The carbon nanotube conductive adhesive CNT-PANM is used. The conductive adhesive is formed by the modified carbon nanotube and the acrylic terpolymer PANM through the outer wall grafting and connection with the carbon nanotube through the grafting of PANM to form a stable conductive network, thereby improving the conductivity and adhesion of the silicon-based negative electrode.
CNT-PANM significantly reduces the impedance of the battery, improves the peel strength and cycling performance of the silicon-based negative electrode, enhances the battery's magnification and discharge capacity retention rate, and extends the battery's service life.
Smart Images

Figure CN119752405A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the field of lithium ion batteries, and in particular to a carbon nanotube conductive binder suitable for silicon-based negative electrodes, a synthesis method and an application thereof. Background Art
[0002] Lithium-ion batteries are widely used in electric vehicles, rail transit, aerospace portable electronic products and other fields due to their high specific capacity, long cycle life, low self-discharge, and environmental friendliness. At present, the specific capacity of lithium-ion batteries using traditional materials such as lithium iron phosphate and graphite is close to the theoretical maximum value, but the cruising range of electric vehicles is still far behind that of gasoline vehicles. Range anxiety is an important reason that limits the wider popularization of electric vehicles. Therefore, the use of positive and negative electrode materials with higher specific energy is an important method to increase the capacity of lithium-ion batteries. Among the negative electrode materials, silicon-based materials are highly expected. The theoretical gram capacity of pure silicon materials is 3578mAh / g. At the same time, silicon-based negative electrode materials also have the following advantages: First, the silicon content is rich and pollution-free to the environment, and the raw materials and preparation costs are relatively low; second, silicon will form an alloy with a high lithium content after lithium embedding, and silicon can provide channels for lithium ion embedding and extraction from all directions, which is beneficial to improving the fast charging performance of the battery; third, the working potential of silicon is moderate (0.3-0.4Vvs Li / Li + ), which is slightly higher than graphite (0.2V), which solves the problem of lithium plating and ensures safety performance.
[0003] Silicon-based anodes have many irreplaceable advantages, but there are also some problems that hinder their large-scale application. The main problems are as follows: First, during the lithium insertion process, Si will produce a volume expansion that exceeds 4 times of Si's own volume, generating large stress, causing the silicon anode to pulverize and break away from the current collector, resulting in specific capacity decay; second, during the first lithium insertion process, silicon and electrolyte undergo an irreversible reaction, forming a passivation SEI film on the surface of the silicon anode, and the volume expansion effect of silicon during the continuous lithium removal / insertion process will cause the SEI film to continuously break and form, consuming electrolyte and active substances, resulting in rapid specific capacity decay; third, silicon itself is a semiconductor material with poor intrinsic conductivity (1×10 –3 S / cm), which affects the transmission of electrons and is the main reason for the poor rate performance.
[0004] At present, one of the simplest ways to promote the application of silicon-based negative electrodes is to use high-performance electrode binders and conductive agents. Electrode binders can effectively inhibit expansion, maintain high capacity of silicon negative electrodes, improve battery cycle performance, and are easy to prepare and industrialize. High-performance conductive agents have excellent conductivity and can also significantly reduce impedance. Only a small amount of addition is enough to form an efficient three-dimensional highly conductive network in the electrode and achieve the goal of increasing battery energy density. Therefore, conductive electrode binders are an important means to solve key problems such as large expansion rate and low conductivity of silicon-based negative electrodes.
[0005] Polyacrylic acid and carbon nanotubes have been used in silicon-based negative electrodes due to their excellent bonding and conductive properties. Polyacrylic acid contains many oxygen-containing groups in its molecular chain, which can form hydrogen bonds with the surface of active materials, giving the active materials and current collectors a strong binding force, while also alleviating the volume expansion of silicon-carbon materials, which can improve the battery's cycle performance. Carbon nanotubes have excellent electrical conductivity that can significantly reduce impedance, and their unique network structure can effectively connect more active substances; in addition, carbon nanotubes with a larger aspect ratio have a large specific surface area. Compared with traditional conductive agents Super-P and graphite, carbon nanotubes only need a small amount of addition to form a three-dimensional high-conductivity network in the electrode and achieve the goal of increasing battery energy density.
[0006] The introduction of both polyacrylic acid and carbon nanotubes can indeed improve the performance of silicon-based negative electrodes, but simple physical blending still has many problems. Due to the competitive relationship between physical mixed adsorption, the dispersion effect is unstable. When new substances, components and solvents are added, the stable dispersion effect may be broken, and even precipitation, gelation, flocculation and other phenomena may occur, which will greatly reduce the actual use efficiency of the conductive agent, resulting in an increase in the amount added and an increase in cost. At the same time, the battery consistency is poor and the battery life is reduced. In order to achieve better dispersion, strong shear force is often required. Strong mechanical force will break the carbon nanotubes and cause damage to the tube wall, reducing the conductivity of the carbon tubes.
[0007] In order to solve the above problems, a carbon nanotube conductive binder suitable for silicon-based negative electrodes, a synthesis method and an application are proposed. Summary of the invention
[0008] In view of the above problems of the prior art, the present invention aims to provide a carbon nanotube conductive binder and a synthesis method, as well as the application of the carbon nanotube conductive binder in a silicon-based negative electrode of a lithium-ion battery.
[0009] The technical solution adopted by the present invention is specifically as follows:
[0010] The present invention first provides a carbon nanotube conductive adhesive (abbreviated as: CNT-PANM), which is formed by grafting an acrylic terpolymer (PANM) with the outer wall of a modified carbon nanotube, and its structural schematic diagram is as follows:
[0011]
[0012] The acrylic acid terpolymer is formed by polymerizing three monomers: acrylic acid, acrylonitrile and acrylamide.
[0013] The modified carbon nanotubes are hydroxylated carbon nanotubes (CNT-OH), that is, carbon nanotubes having hydroxyl functional groups on the surface.
[0014] Furthermore, in the CNT-PANM, the mass ratio of PANM to modified carbon nanotubes is (5-30):1.
[0015] The present invention also provides a method for synthesizing the carbon nanotube conductive adhesive, comprising the following steps:
[0016] 1) Preparation of modified carbon nanotubes
[0017] The carbon nanotubes are added to the reactor and stirred, H2O2 is added dropwise to oxidize the carbon nanotubes, and then filtered, washed, and dried to obtain the modified carbon nanotubes, namely the hydroxylated carbon nanotubes (OH-CNT), and the reaction is as follows:
[0018]
[0019] 2) Preparation of PANM
[0020] 2.1) Preparation of PANM by aqueous precipitation method: First, nitrogen is passed through the reaction vessel to deoxygenate, acrylic acid, acrylonitrile and acrylamide monomers are added to the reaction medium water and stirred to form a polymerization system, and NaOH aqueous solution is added to the polymerization system to adjust the pH value.
[0021] 2.2) heating to a high temperature, and after the temperature is stable, adding a water-soluble initiator to the polymerization system to start a water-phase precipitation polymerization reaction; after the reaction is completed, post-treatment is performed to obtain PANM. The polymerization reaction formula is as follows:
[0022]
[0023] 3) Preparation of CNT-PANM
[0024] PANM is dissolved in an inert solvent, modified carbon nanotubes are added and stirred, a catalyst is added to react, and then the carbon nanotube conductive binder (CNT-PANM) is obtained by washing, filtering and drying. The reaction is as follows:
[0025]
[0026] Furthermore, in step 1), the carbon nanotubes are selected from single-walled, double-walled or multi-walled carbon nanotubes, the mass ratio of carbon nanotubes to hydrogen peroxide is 1:(100-150), the oxidation reaction temperature is 35-60° C., and the reaction time is 3-6 hours.
[0027] The filtering, washing and drying described in step 1) comprises: filtering in a vacuum filtration device, washing with dilute hydrochloric acid and distilled water for multiple times until neutral, and then drying.
[0028] Furthermore, in step 2.1), the mass ratio of acrylic acid, acrylonitrile and acrylamide monomers is (5-40):(10-60):(1-25); after adding NaOH aqueous solution to adjust, the pH of the polymer system is 3-4.
[0029] Furthermore, in step 2.2), the temperature is raised to 60-75°C; the water-soluble initiator is selected from persulfates such as potassium persulfate, ammonium persulfate, sodium persulfate, etc., and is added to the polymerization system in step 2.2) in an amount of 0.1-1.0wt% of the total monomers; the reaction time of the aqueous phase precipitation polymerization reaction is 6-9h; the post-treatment refers to: washing with deionized water and filtering to remove unreacted monomers and water-soluble initiators after the reaction is completed, and then vacuum drying.
[0030] Further, in step 3), the inert solvent is selected from N-methylpyrrolidone, dimethyl sulfoxide, 1,4-dioxane, ethylene glycol dimethyl ether, N,N-dimethylformamide, N,N-dimethylacetamide, dimethyl carbonate or diethyl carbonate; the catalyst is concentrated sulfuric acid, concentrated hydrochloric acid, p-toluenesulfonic acid or other medium-strong acid, and the added amount is 1-10% of the mass fraction of PANM; wherein the mass ratio of PANM to modified carbon nanotubes is (5-30):1; the reaction temperature is 50-80°C, and the reaction time is 6-12h; the washing, filtering and drying comprises: washing and filtering the product with deionized water until the filtrate is neutral, and then drying.
[0031] The present invention also provides an application of the carbon nanotube conductive binder. The carbon nanotube conductive binder is used for a silicon-based negative electrode of a lithium-ion battery. The specific application is as follows.
[0032] A lithium-ion battery silicon-based negative electrode, the formula of which includes a silicon-based active material, a thickener, a conductive agent and the carbon nanotube conductive binder. Wherein, according to the mass ratio, silicon-based active material: thickener: conductive agent: carbon nanotube conductive binder = (94.7-97.3): (0.2-0.8): (0.3-1.5): (1.8-3.0), wherein the thickener is sodium carboxymethyl cellulose or polyacrylic acid, and the conductive agent is conductive graphite, conductive carbon black, Ketjen black, graphene, carbon nanotube or SP-Li.
[0033] Compared with the prior art, the present invention has the following advantages:
[0034] The carbon nanotube conductive adhesive provided by the present invention first modifies the outer wall of the carbon nanotube, and polymerizes acrylic acid, acrylonitrile and acrylamide monomers into PANM (acrylic acid terpolymer), and obtains the carbon nanotube conductive adhesive CNT-PANM by grafting the outer wall of the carbon nanotube with PANM, which has good dispersibility in water phase.
[0035] The carbon nanotube conductive adhesive of the present invention is applied to the silicon-based negative electrode of the lithium-ion battery, and is easily dispersed during the slurry stirring process without generating floccules; the prepared silicon-based negative electrode has high peeling strength, and the inner wall of the carbon nanotube is kept intact through the grafting connection between PANM and the carbon nanotube wall, thereby ensuring the excellent conductive performance of the carbon nanotube and significantly reducing the impedance of the battery.
[0036] The PANM structure contains strong polar groups such as ester, nitrile and amino groups. A large number of hydrogen bonds are formed between the strong polar groups and the active materials and current collectors, which enhances the adhesion of the electrodes. At the same time, it can alleviate the impact of the volume expansion of silicon-based materials and greatly improve the rate and cycle performance of silicon-based batteries. BRIEF DESCRIPTION OF THE DRAWINGS
[0037] Figure 1 This is the infrared spectrum of CNT-PANM prepared in Example 1.
[0038] Figure 2 This is an electron microscope image of the CNT-PANM dispersion prepared in Example 1 at 200 nm.
[0039] Figure 3 This is an electron microscope image of a 500nm dispersion formed by physical mixing of CNT and PANM in Comparative Example 1.
[0040] Figure 4 The discharge data graph of the silicon-based negative electrode of Example 1 and Comparative Example 1 after 1500 cycles.
[0041] Figure 5 The discharge data graph of the silicon-based negative electrode of Example 2 and Comparative Example 2 after 1500 cycles.
[0042] Figure 6 The discharge data graph of the silicon-based negative electrode of Example 3 and Comparative Example 3 after 1500 cycles.
[0043] Figure 7 The discharge data graph of the silicon-based negative electrode of Example 4 and Comparative Example 4 after 1500 cycles. DETAILED DESCRIPTION
[0044] The present invention will be further described below in conjunction with the embodiments, but it does not constitute any limitation to the present invention. Any limited number of modifications made within the scope of the claims of the present invention are still within the scope of the claims of the present invention.
[0045] In order to explain the technical content of the present invention in detail, further description is given below in conjunction with the implementation modes.
[0046] In each embodiment of the present invention, carbon nanotubes are modified by hydrogen peroxide to form hydroxylated carbon nanotubes; at the same time, acrylic acid, acrylonitrile, and acrylamide monomers are polymerized to form PANM (acrylic acid terpolymer), and PANM and the modified carbon nanotubes are composited by grafting chemistry to form the carbon nanotube conductive adhesive of the present invention, namely CNT-PANM, whose structural schematic diagram is as follows:
[0047]
[0048] Example 1
[0049] In this embodiment, the CNT-PANM synthesis method is as follows (1) to (3); in step (4), a method for preparing a silicon-based negative electrode using the CNT-PANM prepared in this embodiment as a binder, as well as its application in lithium-ion batteries and related application performance tests are provided; the details are as follows.
[0050] (1) Preparation of modified carbon nanotubes (CNT-OH):
[0051] The carbon nanotubes used in this embodiment are single-walled carbon nanotubes (CNTs). The single-walled carbon nanotubes are added to a reaction bottle and placed on a stirrer. H2O2 is added dropwise at a mass ratio of 1:150 for single-walled carbon nanotubes:H2O2, and the mixture is stirred and reacted at 60°C for 3h. The reaction product is filtered with 0.45μm filter paper in a vacuum filtration device. In order to remove impurities, the filtered reaction product is washed several times with 5% dilute hydrochloric acid and distilled water until the pH value is 7. Then it is dried in an oven at 60°C for 12h to obtain modified carbon nanotubes.
[0052] (2) Preparation of PANM
[0053] PANM was prepared by aqueous precipitation method. First, nitrogen was passed through the reaction vessel to deoxygenate for 30 minutes, and the distilled acrylonitrile and acrylamide monomers were added to the reaction medium water in a mass ratio of 40:60:25 and stirred, and a 20% concentration of NaOH aqueous solution was added to adjust the pH value of the polymerization system to 3-4, and the temperature was raised to 69°C. After stabilization, water-soluble initiator ammonium persulfate (accounting for 1.0wt% of the total monomers) was added to start aqueous precipitation polymerization reaction, and the reaction was carried out for 7.5 hours. After the reaction was completed, it was washed and filtered with deionized water to remove unreacted monomers and initiators, and then fully dried under vacuum conditions at 80°C to finally obtain PANM.
[0054] (3) Preparation of CNT-PANM
[0055] PANM was placed in a round-bottom flask, and N-methylpyrrolidone solvent was added to completely dissolve it. Then, the modified carbon nanotubes were added in a mass ratio of 25:1 (PANM: modified carbon nanotubes) and stirred to fully mix them. Concentrated sulfuric acid (accounting for 10% of the mass fraction of PANM) was added and reacted at 65°C for 10 hours. The product was washed and filtered until the filtrate was neutral, i.e., the pH value was 7, and then dried at 50°C to obtain the carbon nanotube conductive adhesive of this embodiment, i.e., CNT-PANM.
[0056] The CNT-PANM prepared in this example was subjected to thermogravimetric analysis, and it was found that the weight loss of the sample between 300 and 550°C was 96.2%, and the weight loss in this range can be regarded as the total amount of PANM in the sample. From the thermogravimetric results, it can be concluded that the mass ratio of PANM to modified carbon nanotubes is 25:1, which is consistent with the mass ratio added during preparation.
[0057] like Figure 1 is the infrared spectrum of CNT-PANM prepared in this embodiment, in which CNT, CNT-OH, and CNT-PANM respectively represent the raw material single-walled carbon nanotubes used in this embodiment, the modified carbon nanotubes prepared in step 1), and the carbon nanotube conductive adhesive prepared in this embodiment. 1700 cm -1 The absorption peak at 1500cm is caused by the stretching vibration of the CO double bond in the ester group. -1 The absorption peak at 1050 cm is due to the antisymmetric stretching vibration of COO-, while the C—O—C stretching vibration absorption peak in the ester molecule appears near 1050 cm. The absorption peak is obvious, which preliminarily indicates that the esterification reaction is successful, that is, the modified carbon nanotubes and PANM are successfully grafted chemically.
[0058] (4) Preparation of silicon-based anode and assembly of lithium-ion batteries
[0059] The carbon nanotube conductive binder prepared above is applied to the silicon-based negative electrode of the lithium-ion battery. The specific application method is as follows:
[0060] 4.1) Preparation of CNT-PANM dispersion
[0061] The dried CNT-PANM prepared in Example 1 was dispersed in an aqueous solution, a small amount of LiOH aqueous solution was added to adjust the pH value to neutral, and the mixture was stirred at 3500 rpm for 2 h to obtain a CNT-PANM dispersion with a solid content of 35%. Figure 2 This is an electron microscope image of a 200nm CNT-PANM dispersion. It can be seen from the image that the conductive binder is evenly dispersed without the generation of flocculants, which confirms that the CNT-PANM of the present invention has a good dispersibility in the aqueous phase. The uniform dispersion of CNT-PANM avoids the problems of reduced battery consistency and service life caused by the instability of the physical mixing dispersion effect, precipitation, gelation, flocculation and other phenomena in the prior art; it also avoids the problems of using strong shear force to achieve better dispersion in the physical blending method, causing the carbon nanotubes to break and damage the tube wall, thereby reducing the conductivity of the carbon tubes.
[0062] 4.2) Preparation of silicon-based negative electrode sheets for lithium-ion batteries
[0063] In this embodiment, the formula for preparing the silicon-based negative electrode of the lithium-ion battery is: using 500mAh / g silicon-carbon active material, a thickener (sodium carboxymethyl cellulose), a conductive agent (SP-Li) and the carbon nanotube conductive binder (CNT-PANM) prepared in this embodiment, according to the mass ratio, 500mAh / g silicon-carbon active material: sodium carboxymethyl cellulose: SP-Li: CNT-PANM = 97.3:0.30:0.60:1.80. According to this formula ratio, the specific preparation process is as follows.
[0064] Silicon-based negative electrode sheet preparation process:
[0065] First, deionized water and a thickener are added to stir to prepare a 1.5% solid content glue solution. At the same time, the silicon-carbon active material and the conductive agent are added to a planetary mixer in proportion and dry mixed for 30 minutes. Then the stirred glue solution is added to the planetary mixer for kneading, and deionized water is added to adjust the solid content to 65%. The planetary mixer revolves at 45 rpm and rotates at 400 rpm for 80 minutes. Then, the CNT-PANM dispersion prepared in step 1) of this embodiment is added for stirring and dispersion, and water is added to adjust the viscosity to ensure that the viscosity of the discharge slurry is 3000-4000 mPa.s. During this process, the planetary mixer revolves at 45 rpm and rotates at 2500 rpm. The stirring and dispersion time is 2 hours, until there are no particles protruding from the surface when the slurry is applied. Cooling water is turned on during the stirring process to control the stirring temperature at 25°C. Finally, vacuum is evacuated for defoaming to obtain a silicon-based negative electrode slurry. The silicon-based negative electrode slurry is coated and dried using an intermittent experimental coating machine, and then the electrode sheet is rolled using a roller press to obtain a silicon-based negative electrode sheet of the required thickness. The roller compaction density is 1.6g / cm3 .
[0066] 4.3) Assemble the battery
[0067] The positive electrode sheet and the silicon-based negative electrode sheet prepared in step 4.2) are paired, with the negative electrode capacity exceeding 10%, and a silicon-based lithium-ion battery is prepared by stacking, and the performance is tested.
[0068] In this embodiment, the positive electrode plate is prepared by the following method: the positive electrode slurry formula is ternary 811: SP-Li: CNT: PVDF = 96: 1.5: 1.0: 1.5, first add PVDF and NMP to prepare a PVDF glue with a solid content of 3.8%, after completion, add the PVDF glue and CNT into a planetary mixer and stir and disperse for 60 minutes, revolve at 45 rpm, and rotate at 2500 rpm, then add SP-Li into the planetary mixer and stir and disperse for 60 minutes, revolve at 45 rpm, and rotate at 2500 rpm, after completion, add the ternary 811 material and NMP and start stirring and dispersing for 150 minutes, revolve at 45 rpm, and rotate at 3500 rpm to ensure that the discharge viscosity is 6000-8000 mPa.s, open cooling water throughout the stirring process to control the stirring temperature at 25°C, and evacuate and maintain the pressure at -0.1 MPa throughout the process to obtain a ternary positive electrode slurry. The ternary positive electrode slurry was coated and dried using an intermittent experimental coating machine, and then the electrode sheet was rolled using a roller press to obtain a ternary positive electrode sheet of the required thickness. The roller compaction density was 3.4g / cm 3 .
[0069] Example 2
[0070] Using the carbon nanotube conductive binder (CNT-PANM) prepared in Example 1, the same method and steps as in Example 1 were adopted to prepare a silicon-based negative electrode, a ternary positive electrode and assembled silicon-based batteries. The difference was that the formula of the silicon-based negative electrode was different. According to the mass ratio, the formula of the silicon-based negative electrode in this embodiment was 500mAh / g silicon-carbon active material: sodium carboxymethyl cellulose: SP-Li: CNT-PANM = 96.9:0.30:0.60:2.2.
[0071] Example 3
[0072] Using the carbon nanotube conductive binder (CNT-PANM) prepared in Example 1, the same method and steps as in Example 1 were adopted to prepare a silicon-based negative electrode, a ternary positive electrode and assembled silicon-based batteries. The difference was that the formula of the silicon-based negative electrode was different. According to the mass ratio, the formula of the silicon-based negative electrode in this embodiment was 500mAh / g silicon-carbon active material: sodium carboxymethyl cellulose: SP-Li: CNT-PANM = 96.5:0.30:0.60:2.6.
[0073] Example 4
[0074] Using the carbon nanotube conductive binder (CNT-PANM) prepared in Example 1, the same method and steps as in Example 1 were adopted to prepare a silicon-based negative electrode, a ternary positive electrode and assembled silicon-based batteries. The difference was that the formula of the silicon-based negative electrode was different. According to the mass ratio, the formula of the silicon-based negative electrode in this embodiment was 500mAh / g silicon-carbon active material: sodium carboxymethyl cellulose: SP-Li: CNT-PANM = 96.1:0.30:0.60:3.0.
[0075] Comparative Example 1
[0076] In this comparative example 1, the single-walled carbon nanotubes (CNT) used in step 1) of Example 1 and the PANM prepared in step 2) of Example 1 were physically mixed to prepare a mixed dispersion of CNT and PANM as a binder. The preparation process of the mixed dispersion of CNT and PANM is as follows:
[0077] Single-walled carbon nanotubes CNT and PANM were added to an aqueous solution, wherein the mass ratio of the two was PANM:CNT = 25:1, and then a small amount of LiOH aqueous solution was added to adjust the pH value to neutral, and stirred at 3500 rpm for 2 hours to obtain a CNT and PANM mixed dispersion with a solid content of 35%. Figure 3 This is an electron microscope image of a 500nm CNT and PANM mixed dispersion of this embodiment. From the image, it can be seen that some CNT particles are aggregated together and are not completely dispersed.
[0078] The above CNT and PANM mixed dispersion was used as a binder to prepare a silicon-based negative electrode. In this comparative example, the formula for preparing a silicon-based negative electrode is: 500mAh / g silicon-carbon active material, thickener sodium carboxymethyl cellulose, conductive agent SP-Li and binder (CNT and PANM mixed dispersion prepared in this comparative example) are used to prepare a silicon-based negative electrode. According to the mass ratio, silicon-carbon active material: sodium carboxymethyl cellulose: SP-Li: PANM: CNT = 97.3: 0.30: 0.60: 1.731: 0.069, wherein the mass ratio of PANM: carbon nanotubes is equivalent to 25: 1. According to this formula ratio, the specific preparation process is as follows.
[0079] First, add deionized water and thickener to stir to prepare a glue solution with a solid content of 1.5%. At the same time, add silicon-carbon active material and conductive agent SP-Li according to proportion into a planetary mixer and dry mix for 30 minutes. Then add the stirred glue solution into the planetary mixer for kneading. Add deionized water to adjust the solid content to 65%. The planetary mixer revolves at 45 rpm and rotates at 400 rpm for 80 minutes. After completion, add CNT and PANM mixed dispersion, stir and disperse, add water to adjust the viscosity, and ensure that the viscosity of the discharged slurry is between 3000 and 4000 mPa.s. The planetary mixer for stirring and dispersing revolves at 45 rpm and rotates at 3500 rpm for 2 hours. When the slurry is applied, there are no protruding particles on the surface. Cold water is used to control the stirring temperature at 25°C during the whole stirring process. Finally, vacuum is evacuated to defoam and obtain silicon-based negative electrode slurry. The silicon-based negative electrode slurry was coated and dried using an intermittent experimental coating machine, and then the electrode sheet was rolled using a roller press to obtain a silicon-based negative electrode sheet of the required thickness. The rolling compaction density was 1.6 g / cm 3 .
[0080] Then, the lithium-ion battery was assembled and tested for performance: the positive electrode sheet and the negative electrode sheet were paired, the negative electrode capacity was 10% excessive, and the silicon-based battery was prepared by lamination for performance testing. The positive electrode sheet was prepared in the same way as in the embodiment.
[0081] Comparative Example 2
[0082] The same method and steps as those in Comparative Example 1 were used to prepare a silicon-based negative electrode, a ternary positive electrode and assembled silicon-based batteries. The difference was that the formula of the silicon-based negative electrode was different. According to the mass ratio, the silicon-based negative electrode formula of this comparative example was 500mAh / g silicon-carbon active material: sodium carboxymethyl cellulose: SP-Li: PANM: CNT = 96.9: 0.30: 0.60: 2.115: 0.085, wherein the mass ratio of PANM: carbon nanotubes was 25:1.
[0083] Comparative Example 3
[0084] The same method and steps as those in Comparative Example 1 were used to prepare a silicon-based negative electrode, a ternary positive electrode and an assembled battery. The difference was that the formula of the silicon-based negative electrode was different. According to the mass ratio, the silicon-based negative electrode formula of this comparative example was 500mAh / g silicon-carbon active material: sodium carboxymethyl cellulose: SP-Li: PANM: CNT = 96.5: 0.30: 0.60: 2.50: 0.10, wherein the mass ratio of PANM: carbon nanotubes was 25:1.
[0085] Comparative Example 4
[0086] The same method and steps as those in Comparative Example 1 were used to prepare a silicon-based negative electrode, a ternary positive electrode and an assembled battery. The difference was that the formula of the silicon-based negative electrode was different. According to the mass ratio, the silicon-based negative electrode formula of this comparative example was 500mAh / g silicon-carbon active material: sodium carboxymethyl cellulose: SP-Li: PANM: CNT = 96.1: 0.30: 0.60: 2.885: 0.115, wherein the mass ratio of PANM: carbon nanotubes was 25: 1; in the slurry mixing process of this comparative example, there were some black floccules that were insoluble in water, and the material was filtered with a 100-mesh filter when discharged.
[0087] Comparison of test performance of each embodiment and comparative example:
[0088] 1) Peel strength test
[0089] The silicon-based negative electrode sheets after rolling of Examples 1-4 and Comparative Examples 1-4 were cut into 30×200 mm rectangular samples and subjected to peel strength test using a tensile testing machine with a tensile speed of 100 mm / min, a width of 30 mm, and a load of 0.05 mN.
[0090] It can be seen from the data in Table 1 that in each embodiment and comparative example, as the mass ratio of the binder content in the silicon-based negative electrode increases, the peel strength is constantly increasing; in addition, in embodiments 1-3 and comparative examples 1-3, embodiment 1 and comparative example 1, embodiment 2 and comparative example 2, embodiment 3 and comparative example 3, the binder is in the same mass ratio in the silicon-based negative electrode pole piece. In this case, the peel strength of the embodiment and the comparative example does not change much; however, as the mass ratio of the binder in the silicon-based negative electrode continues to increase, the peel strength begins to show obvious differences, and the embodiment continues to increase steadily, and the increase is significantly smaller than that of the comparative example. For example, the data of embodiment 4 and comparative example 4 in Table 1 show that the peel strength of the two is significantly different. The difference is that Example 4 is 6N / m higher than Comparative Example 4, and their binders use the same mass proportion in the silicon-based negative electrode. This is because for the physical mixing of CNT and PANM in the comparative example, the silicon-based negative electrode slurry in Comparative Example 4 has a high content of carbon nanotubes. In the physical mixing, due to the competitive relationship between physical mixing adsorption, the high content of carbon nanotubes is difficult to disperse, and its dispersion effect is unstable. During the mixing, the original stable dispersion effect of the physical mixing of CNT and PANM is broken. Some black floccules are generated during the stirring and dispersion process. After filtering through the filter screen, the ratio of effective binder and conductive agent decreases, and the corresponding peel strength is much different from that of Example 4 with the same ratio of binder. This comparison also reflects that the carbon nanotube conductive binder (CNT-PANM) of the present invention has good dispersibility in the water phase, which avoids the above-mentioned problems of physical mixing in the comparative example, and further avoids the problem of reducing battery consistency and service life caused by the phenomenon of uneven dispersion.
[0091] Table 1 Test data of peel strength of silicon-based negative electrode sheets of Examples 1-4 and Comparative Examples 1-4
[0092]
[0093]
[0094] 2) DC resistance test
[0095] Test steps: Use Xinwei battery testing equipment, charge with 0.33C current, constant current and constant voltage until the limit voltage reaches 4.2V, and the charging ends when the cut-off current drops to 0.05C; with 0.33C current, leave it at 25℃ for 10min, and discharge with constant current until the cut-off voltage reaches 2.5V, and the discharge ends, taking this as the initial capacity, and leave it for 10min; charge with 0.33C current, constant current and constant voltage until the limit voltage reaches 4.2V, and the charging ends when the cut-off current drops to 0.05C, leave it at 25℃ for 10min, and discharge with 0.5C constant current for 1h, and reach 50% state of charge. Adjust the state of charge according to the above steps, discharge at 4C current for 30s at 25℃, and discharge at 0.33C current for 30s at -20℃, and calculate the DC resistance by the voltage difference and current. The DC resistance calculation formula is: DC resistance = voltage difference / test current. The data in Table 2 below were measured.
[0096] Table 2. DC resistance test data of Examples 1-4 and Comparative Examples 1-4
[0097] Experimental batch 4C / 30s, 25℃(mΩ) 0.33C / 30s, -25℃(mΩ) Example 1 74 988 Comparative Example 1 78 1043 Example 2 71 942 Comparative Example 2 76 1002 Example 3 65 875 Comparative Example 3 73 980 Example 4 57 812 Comparative Example 4 71 961
[0098] From the data in Table 2, it can be seen that the DC resistance of Example 1 is 4 mΩ less than that of Comparative Example 1 at 25°C, and 55 mΩ less at low temperature -25°C; the DC resistance of Example 2 is 5 mΩ less than that of Comparative Example 2, and 60 mΩ less at low temperature -25°C; the DC resistance of Example 3 is 8 mΩ less than that of Comparative Example 3, and 105 mΩ less at low temperature -25°C; the DC resistance of Example 4 is 13 mΩ less than that of Comparative Example 4, and 149 mΩ less at low temperature -25°C. Under the same proportion of carbon nanotube content, the DC resistance of the carbon nanotube conductive binder (CNT-PANM) (each embodiment) of the technical solution of the present invention is smaller than that of the physical mixing method (comparative example) in the prior art, and as the mass proportion of carbon nanotubes in the silicon-based negative electrode increases, under the same proportion of carbon nanotube content, the difference in DC resistance between the technical solution of the present invention (each embodiment) and the physical mixing (comparative example) is greater. This is because in each comparative example, the dispersion of carbon nanotubes requires a strong shear force. During the long stirring process, the strong shear force will cause some carbon nanotubes to break and cause damage to the tube wall, reducing the conductivity of the carbon tube; in contrast, the carbon nanotube conductive binder (CNT-PANM) of the present invention is grafted and connected to the outer wall of the modified carbon nanotube by PANM in the binder, so that the inner wall of the carbon nanotube remains intact, and CNT-PANM does not require high-intensity shear force to be evenly dispersed, so that the carbon nanotubes can form an efficient three-dimensional highly conductive network in the electrode, greatly reducing the internal resistance of the battery. For example: when preparing silicon-based negative electrode slurry, each embodiment needs to revolve 45rpm and rotate 2500rpm in the mixing process, compared with the comparative example, the mixing process needs to revolve 45rpm and rotate 3500rpm.
[0099] 3) Rate discharge test
[0100] Using Xinwei battery test equipment, at 25℃, charge at 0.33C current, constant current and constant voltage until the limit voltage reaches 4.2V, and the charging ends when the cut-off current drops to 0.05C; leave for 5 minutes; discharge at 0.33C current, constant current until the cut-off voltage reaches 2.5V, and the discharge ends, which is the initial capacity; leave for 5 minutes; repeat the above charging operation, and then discharge at 1C, 3C, and 5C rates to the cut-off voltage of 2.5V; leave for 5 minutes; after the end, record the discharge capacity of different rate currents. The measured data is shown in Table 3.
[0101] Table 3. Discharge capacity data of Examples 1-4 and Comparative Examples 1-4 at different rates
[0102]
[0103]
[0104] It can be seen from Table 3 that the discharge capacity of the embodiment and the comparative example at a low rate of 1C discharge current is not much different, but as the discharge current increases, the discharge capacity begins to change significantly. For example, at 3C discharge, the discharge capacity retention rate of embodiment 1 is 4.44% higher than that of comparative example 1; the discharge capacity retention rate of embodiment 2 is 3.60% higher than that of comparative example 2; the discharge capacity retention rate of embodiment 3 is 5.07% higher than that of comparative example 4; and the discharge capacity retention rate of embodiment 4 is 5.55% higher than that of comparative example 4. At 5C discharge, the discharge capacity retention rate of embodiment 1 is 5.02% higher than that of comparative example 1; the discharge capacity retention rate of embodiment 2 is 7.00% higher than that of comparative example 2; the discharge capacity retention rate of embodiment 3 is 6.50% higher than that of comparative example 4; and the discharge capacity retention rate of embodiment 4 is 7.59% higher than that of comparative example 4. It can be seen that with the increase of the content of carbon nanotube conductive binder (CNT-PANM), the battery impedance is constantly decreasing, the polarization is reduced during the charge and discharge process, and the discharge capacity retention rate is gradually increasing; when containing the same proportion of binder and carbon nanotubes, the capacity of the embodiment is stronger than that of the comparative example. This is because the carbon nanotubes in the physically composite binder in the comparative example are difficult to disperse evenly, and some carbon nanotubes break and cause tube wall damage under high shear force, resulting in a reduction in effective conductive agent, causing the comparative example to have increased polarization and reduced discharge capacity at a high rate discharge current.
[0105] 4) Cycle performance test
[0106] Using Xinwei battery test equipment, at 25℃, charge at 0.5C current, constant current and constant voltage until the limit voltage reaches 4.2V, and the charging ends when the cut-off current drops to 0.05C; leave it for 5 minutes; discharge at 1C current and constant current until the cut-off voltage reaches 2.5V, and the discharge ends. Perform 1500 cycles of charge and discharge, and record the discharge capacity of each cycle after the end. The test results are as follows Figure 4-Figure 7 .
[0107] pass Figure 4-Figure 7 It can be seen that the discharge capacities of the embodiment and the comparative example are similar in the first 400 cycles, but as the number of cycles increases, the discharge capacity of the comparative example decreases rapidly relative to that of the embodiment. At 1500 cycles, the capacity retention rate of the embodiment 1 is 84.27%, and the capacity retention rate of the comparative example 1 is 74.82%, with a difference of 9.45% ( Figure 4 ); The capacity retention rate of Example 2 is 86.97%, and the capacity retention rate of Comparative Example 2 is 76.87%, a difference of 10.10% ( Figure 5 ); The capacity retention rate of Example 3 is 90.56%, and the capacity retention rate of Comparative Example 3 is 79.35%, a difference of 11.21% ( Figure 6 ); The capacity retention rate of Example 4 is 91.26%, and the capacity retention rate of Comparative Example 4 is 80.13%, a difference of 11.13%
[0108] ( Figure 7 ). By comparison, it is found that under the same proportion of carbon nanotubes and binders, the carbon nanotube conductive binder (embodiment) of the present invention has better cycle performance than the binder (comparative example) obtained by physical mixing. This is because the carbon nanotube conductive binder (CNT-PANM) of the present invention is grafted and connected by the binder PANM and the modified carbon nanotube wall, and the inner wall of the carbon nanotube remains intact, which ensures the excellent conductivity of the carbon nanotube. At the same time, the binder PANM structure contains ester, nitrile, and amino strong polar groups, and a large number of hydrogen bonds are formed between the strong polar groups and the active materials and the current collector, which enhances the adhesion of the electrode, and can also alleviate the influence of the volume expansion of the silicon-based material, which can greatly improve the cycle performance of the silicon-based battery.
[0109] Through the above comparative data of Examples 1-4 and Comparative Examples 1-4, it can be found that when the same proportion of binder is used in the silicon-based negative electrode, the test data of the examples are better than those of the comparative examples, and the advantage is more obvious when the carbon nanotube conductive binder (CNT-PANM) accounts for 3% by mass in the silicon-based negative electrode (Example 4), so the subsequent examples are based on the silicon-based negative electrode formula in which the carbon nanotube conductive binder (CNT-PANM) accounts for 3% and the mass of CNT and PANM in the comparative example also accounts for 3% by mass in the silicon-based negative electrode (the same as Comparative Example 4) for performance testing.
[0110] Example 5
[0111] In this embodiment, the CNT-PANM synthesis method is as follows (1) to (3); in step (4), a method for preparing a silicon-based negative electrode using the CNT-PANM prepared in this embodiment as a binder, as well as its application in lithium-ion batteries and related application performance tests are provided; the details are as follows.
[0112] (1) Preparation of modified carbon nanotubes (CNT-OH)
[0113] Add double-walled carbon nanotubes to a reaction bottle and place it on a stirrer. Add H2O2 at a mass ratio of 1:100 (double-walled carbon nanotubes: H2O2), stir and mix, and react at 35°C for 6 hours. The product is filtered with 0.45μm filter paper in a vacuum filtration device. In order to remove impurities, wash with 5% dilute hydrochloric acid and distilled water several times until the pH value is 7. After washing, dry in an oven at 60°C for 12h to obtain modified carbon nanotubes.
[0114] (2) Preparation of PANM
[0115] PANM was prepared by an aqueous precipitation method. Before the polymerization began, nitrogen was passed to deoxygenate for 30 minutes. The distilled acrylonitrile and acrylamide monomers were added to the reaction medium water in a mass ratio of 5:60:1 and stirred. At the same time, a 20% concentration of NaOH aqueous solution was added to adjust the pH value of the polymerization system to 3-4. The temperature was heated to 60°C. After stabilization, a water-soluble initiator sodium persulfate (accounting for 0.1wt% of the total monomers) was added to start an aqueous precipitation polymerization reaction. The reaction was carried out for 9 hours. After the reaction was completed, it was washed and filtered with deionized water to remove unreacted monomers and initiators, and then fully dried under vacuum conditions at 80°C to finally obtain PANM.
[0116] (3) Preparation of CNT-PANM
[0117] PANM was placed in a round-bottom flask, and N,N-dimethylformamide solvent was added to completely dissolve it. Then, modified carbon nanotubes were added in a mass ratio of 5:1 (PANM: modified carbon nanotubes), stirred to make them fully mixed, and p-toluenesulfonic acid (accounting for 1% of the mass fraction of PANM) was added. The reaction was carried out at 50°C for 12 hours. The product was washed and filtered until the filtrate was neutral, and then dried at 50°C.
[0118] The CNT-PANM prepared in this example was subjected to thermogravimetric analysis, and the results showed that the mass ratio of PANM to modified carbon nanotubes was 5:1.
[0119] (4) Application of carbon nanotube conductive binder (CNT-PANM) in silicon-based anode
[0120] The carbon nanotube conductive binder (CNT-PANM) prepared in this embodiment is used in a silicon-based negative electrode, and a silicon-based negative electrode, a ternary positive electrode and an assembled silicon-based battery are prepared by the same method and steps as in Example 1. The difference is that the formula of the silicon-based negative electrode is different: 500mAh / g silicon-carbon active material, a thickener (polyacrylic acid), a conductive agent (conductive graphite KS6) and the carbon nanotube conductive binder (CNT-PANM) of this embodiment are used. According to the mass ratio, the silicon-based negative electrode formula is 500mAh / g silicon-carbon active material: polyacrylic acid: conductive graphite KS6: CNT-PANM=96.5:0.2:0.3:3.0.
[0121] Comparative Example 5
[0122] The same method and steps as those in Comparative Example 1 were used to prepare a silicon-based negative electrode, a ternary positive electrode and assembled silicon-based batteries. The difference was that the formula of the silicon-based negative electrode was different. According to the mass ratio, the silicon-based negative electrode formula of this comparative example was 500mAh / g silicon-carbon active material: polyacrylic acid: conductive graphite KS6: PANM: CNT = 96.5:0.2:0.3:2.5:0.5, which was equivalent to a PANM: carbon nanotube mass ratio of 5:1.
[0123] Performance Test of Example 5 and Comparative Example 5
[0124] 1) In the peel strength test, the peel strength of Example 5 is 22 N / m, and the peel strength of Comparative Example 5 is 14 N / m. Example 5 is 9 N / m higher than Comparative Example 5.
[0125] 2) In the DC resistance test, at 25°C, the DC resistance of Example 5 is 50mΩ, and the DC resistance of Comparative Example 5 is 60mΩ, and the DC resistance of Example 5 is reduced by 16.67% compared with that of Comparative Example 5; at a low temperature of -25°C, the DC resistance of Example 5 is 786mΩ, and the DC resistance of Comparative Example 5 is 889mΩ, and the DC resistance of Example 5 is reduced by 11.59% compared with that of Comparative Example 5.
[0126] 3) In the rate discharge test, at a discharge current rate of 1C, the capacity retention rate of Example 5 is 99.00%, the capacity retention rate of Comparative Example 5 is 98.48%, and the discharge capacity retention rate of Example 5 is 0.52% higher than that of Comparative Example 5; at a discharge current rate of 3C, the capacity retention rate of Example 5 is 96.89%, the capacity retention rate of Comparative Example 5 is 90.54%, and the discharge capacity retention rate of Example 5 is 6.35% higher than that of Comparative Example 5; at a discharge current rate of 5C, the capacity retention rate of Example 5 is 88.03%, the capacity retention rate of Comparative Example 5 is 79.25%, and the discharge capacity retention rate of Example 5 is 8.78% higher than that of Comparative Example 5.
[0127] 4) In the cycle performance test, when the charge and discharge cycle reaches 1500 cycles, the capacity retention rate of Example 5 is 92.69%, and the capacity retention rate of Comparative Example 5 is 81.56%, with a difference of 11.13%.
[0128] Example 6
[0129] In this embodiment, the CNT-PANM synthesis method is as follows (1) to (3); in step (4), a method for preparing a silicon-based negative electrode using the CNT-PANM prepared in this embodiment as a binder, as well as its application in lithium-ion batteries and related application performance tests are provided; the details are as follows.
[0130] (1) Preparation of modified carbon nanotubes
[0131] Add multi-walled carbon nanotubes to a reaction bottle and place it on a stirrer. Add H2O2 dropwise at a mass ratio of 1:121 (multi-walled carbon nanotubes: H2O2), stir and mix, and react at 50°C for 4 hours. The product is filtered using 0.45μm filter paper in a vacuum filtration device. In order to remove impurities, wash with 5% dilute hydrochloric acid and distilled water several times until the pH value is 7. After washing, dry in an oven at 60°C for 12 hours to obtain modified carbon nanotubes.
[0132] (2) Preparation of PANM
[0133] PANM was prepared by an aqueous precipitation method. Before the polymerization began, nitrogen was passed through the system to deoxygenate for 30 minutes. The distilled acrylonitrile and acrylamide monomers were added to the reaction medium water in a mass ratio of 40:10:1 and stirred. At the same time, a 20% concentration of NaOH aqueous solution was added to adjust the pH value of the polymerization system to 3-4. The system was heated to 75°C. After stabilization, a water-soluble initiator potassium persulfate (accounting for 0.4wt% of the total monomers) was added to start an aqueous precipitation polymerization reaction. The reaction was carried out for 6 hours. After the reaction was completed, the system was washed and filtered with deionized water to remove unreacted monomers and initiators. The system was then fully dried under vacuum conditions at 80°C to finally obtain PANM.
[0134] (3) Preparation of CNT-PANM
[0135] PANM was placed in a round-bottom flask, and dimethyl sulfoxide solvent was added to completely dissolve it. Then, the modified carbon nanotubes were added in a mass ratio of 30:1 (PANM: modified carbon nanotubes) and stirred to make them fully mixed. Phosphoric acid (5% of the mass fraction of PANM) was added and reacted at 80°C for 6h. The product was washed and filtered until the filtrate was neutral, and then dried at 50°C.
[0136] The CNT-PANM prepared in this example was subjected to thermogravimetric analysis, and the results showed that the mass ratio of PANM to modified carbon nanotubes was 30:1.
[0137] (4) Application of carbon nanotube conductive binder (CNT-PANM) in silicon-based anode
[0138] The carbon nanotube conductive binder (CNT-PANM) prepared in this embodiment is used in the silicon-based negative electrode. The silicon-based negative electrode, the ternary positive electrode and the assembled silicon-based battery are prepared by the same method and steps as in Example 1. The difference is that the formula of the silicon-based negative electrode is different. The formula of the silicon-based negative electrode in this embodiment: 500mAh / g silicon-carbon active material, thickener (polyacrylic acid), conductive agent (SP-Li) and the carbon nanotube conductive binder (CNT-PANM) of this embodiment are used. According to the mass ratio, the silicon-based negative electrode formula is 500mAh / g silicon-carbon active material: polyacrylic acid: SP-Li: CNT-PANM=94.7:0.8:1.5:3.0.
[0139] Comparative Example 6
[0140] The same method and steps as those in Comparative Example 1 were used to prepare a silicon-based negative electrode, a ternary positive electrode and assembled silicon-based batteries. The difference was that the formula of the silicon-based negative electrode was different. According to the mass ratio, the silicon-based negative electrode formula of this comparative example was 500mAh / g silicon-carbon active material: polyacrylic acid: SP-Li: PANM: CNT = 94.7:0.8:1.5:2.903:0.097, which was equivalent to a PANM: carbon nanotube mass ratio of 30:1.
[0141] Performance Test of Example 6 and Comparative Example 6
[0142] 1) In the peel strength test, the peel strength of Example 6 is 29 N / m, and the peel strength of Comparative Example 6 is 25 N / m. Example 6 is 4 N / m higher than Comparative Example 6.
[0143] 2) In the DC resistance test, at 25°C, the DC resistance of Example 6 is 65mΩ, and the DC resistance of Comparative Example 6 is 72mΩ, and the DC resistance of Example 6 is 9.72% lower than that of Comparative Example 6; at low temperature of -25°C, the DC resistance of Example 6 is 864mΩ, and the DC resistance of Comparative Example 6 is 961mΩ, and the DC resistance of Example 6 is 10.09% lower than that of Comparative Example 6.
[0144] 3) In the rate discharge test, at a discharge current rate of 1C, the capacity retention rate of Example 6 is 98.09%, and the capacity retention rate of Comparative Example 6 is 97.78%, and the discharge capacity retention rate of Example 6 is 0.31% higher than that of Comparative Example 6; at a discharge current rate of 3C, the capacity retention rate of Example 6 is 94.72%, and the capacity retention rate of Comparative Example 6 is 87.99%, and the discharge capacity retention rate of Example 6 is 6.73% higher than that of Comparative Example 6; at a discharge current rate of 5C, the capacity retention rate of Example 6 is 83.26%, and the capacity retention rate of Comparative Example 6 is 75.25%, and the discharge capacity retention rate of Example 6 is 8.01% higher than that of Comparative Example 6.
[0145] 4) In the cycle performance test, when the charge and discharge cycle reaches 1500 cycles, the capacity retention rate of Example 6 is 90.01%, and the capacity retention rate of Comparative Example 6 is 81.23%, with a difference of 8.78%.
[0146] Obviously, the above embodiments are merely examples for the purpose of clear explanation, and are not intended to limit the implementation methods. For those skilled in the art, other different forms of changes or modifications can be made based on the above description. It is not necessary and impossible to list all the implementation methods here. The obvious changes or modifications derived therefrom are still within the scope of protection of the present invention.
Claims
1. A carbon nanotube conductive adhesive, characterized in that: The carbon nanotube conductive adhesive is formed by grafting PANM with the outer wall of modified carbon nanotubes.
2. The carbon nanotube conductive adhesive according to claim 1, characterized in that: The PANM is formed by polymerization of three monomers: acrylic acid, acrylonitrile and acrylamide; The modified carbon nanotubes are hydroxylated carbon nanotubes, that is, carbon nanotubes having hydroxyl functional groups on the surface.
3. The carbon nanotube conductive adhesive according to claim 2, characterized in that: In the carbon nanotube conductive adhesive, the mass ratio of PANM to modified carbon nanotubes is (5-30):
1.
4. The use of a carbon nanotube conductive adhesive according to any one of claims 1 to 3, characterized in that: The carbon nanotube conductive binder is used as a binder for a silicon-based negative electrode.
5. The use of a carbon nanotube conductive adhesive according to claim 4, characterized in that: The silicon-based negative electrode is a silicon-based negative electrode for a lithium-ion battery.
6. The use of a carbon nanotube conductive adhesive according to claim 5, characterized in that: The formula of the silicon-based negative electrode includes a silicon-based active material, a thickener, a conductive agent and The carbon nanotube conductive adhesive; according to the mass ratio, the proportion of each material in the formula Silicon-based active material: thickener; conductive agent: the carbon nanotube conductive binder = (94.7-97.3):(0.2-0.8):(0.3-1.5):(1.8-3.0)。 7. The use of a carbon nanotube conductive adhesive according to claim 6, characterized in that: The thickener is selected from sodium carboxymethyl cellulose or polyacrylic acid, and the conductive agent is selected from Self-conductive graphite, conductive carbon black, Ketjen black, graphene, carbon nanotubes or SP-Li.
8. A method for synthesizing the carbon nanotube conductive adhesive according to any one of claims 1 to 3, characterized in that: The following steps are involved: 1) Preparation of modified carbon nanotubes The carbon nanotubes are added to the reactor and stirred, and H2O2 is added dropwise to perform a modification reaction to oxidize the carbon nanotubes. The modified carbon nanotubes are then filtered, washed, and dried to obtain the modified carbon nanotubes. The reaction formula is as follows: 2) Preparation of PANM 2.1) Preparation of PANM by aqueous precipitation method: First, nitrogen is passed through the reaction vessel to deoxygenate, acrylic acid, acrylonitrile, and acrylamide monomers are added to the reaction medium water and stirred, and NaOH aqueous solution is added to adjust the pH value of the polymerization system; 2.2) heating to a high temperature, adding a water-soluble initiator after the temperature rises steadily to start a water-phase precipitation polymerization reaction; after the reaction is completed, PANM is obtained by post-treatment; the reaction formula is as follows: 3) Preparation of the carbon nanotube conductive adhesive The PANM obtained in step 2) is dissolved in an inert solvent, the modified carbon nanotubes obtained in step 1) are added and stirred, a catalyst is added to react, and then the carbon nano conductive binder is obtained by washing, filtering and drying; the reaction formula is as follows:
9. The method for synthesizing a carbon nanotube conductive adhesive according to claim 8, characterized in that: In step 1), the carbon nanotubes are single-walled, double-walled or multi-walled carbon nanotubes; the mass ratio of carbon nanotubes to H2O2 is 1:(100-150), the modification reaction temperature is 35-60°C, and the reaction time is 3-6h; The filtering, washing and drying in step 1) includes: vacuum filtration, washing with dilute hydrochloric acid and distilled water until neutral, and drying; In step 2.1), the mass ratio of acrylic acid, acrylonitrile and acrylamide monomers is (5-40): (10-60):(1-25), the pH of the polymer system after adjustment by adding NaOH aqueous solution is 3-4; In step 2.2), the water-soluble initiator is selected from potassium persulfate, ammonium persulfate, sodium persulfate or other persulfates, and the added amount is 0.1-1.0wt% of the total monomers; the heating temperature is raised to 60-75°C, and the aqueous phase precipitation polymerization reaction time is 6-9h; the post-treatment is: washing with deionized water, filtering to remove unreacted monomers and water-soluble initiator, and then vacuum drying.
10. The method for synthesizing a carbon nanotube conductive adhesive according to claim 8, characterized in that: In step 3), the inert solvent is selected from N-methylpyrrolidone, dimethyl sulfoxide, 1,4-dioxane, ethylene glycol dimethyl ether, N,N-dimethylformamide, N,N-dimethylacetamide, dimethyl carbonate or diethyl carbonate; the catalyst is concentrated sulfuric acid, concentrated hydrochloric acid, p-toluenesulfonic acid or other medium-strong acid; the catalyst accounts for 1-10% of the mass of PANM, the mass ratio of PANM to modified carbon nanotubes is (5-30): 1, the reaction temperature is 50-80°C, and the reaction time is 6-12h; The washing, filtering and drying in step 3) comprises: washing and filtering the product with deionized water until the filtrate is neutral, and then drying.
Citation Information
Patent Citations
Silicon-oxygen negative electrode material with surface connected with binder, and preparation method and application of silicon-oxygen negative electrode material
CN115799488A
Artificial graphite negative electrode material connected with binder on surface and preparation method and application thereof
CN115799506A
Conductive binder, preparation method and application thereof
CN115939398A
Negative pole piece and electrochemical device
CN115966653A
Modified binder, binder composition, preparation method, negative electrode slurry, negative electrode pole piece, secondary battery, battery module, battery pack and electric device
CN118056292A